Pemanfaatan Serabut Kelapa sebagai Bahan Pembuatan Rangka Drone - Muhammad Ikhsan; Permana, Indra; Pratama, Riza Arif; Setiajit, Sahid Bayu; Assidiqi, Dimas Ahsan; Ramadhani, Sandy Laila Suci (Jurnal Teknik, 2025)
Drones are one of the latest technologies that are developing rapidly to provide positive benefits in society. Drone development can be done in various ways, including by improving the performance of the drone frame. Drone frames can be made of various types of materials, one of which is composite material that has mechanical properties that can be adjusted to needs. In this study, coconut fiber was chosen as the composite material because of its abundant availability, light weight, and environmentally friendly. Coconut fiber composites are made to be one of the alternatives for drone frames. To overcome its low strength, coconut fiber is used together with fiberglass to become a hybrid composite. Tensile tests, bending tests, and impact tests were carried out to determine the mechanical characteristics of the hybrid composite. The test results are then used as the basis for determining the drone design. Two types of tensile test specimens were made using the hand lay-up method where the type of fiber was varied to see the effect of variations in fiber types on the strength of the composite. The first type is a composite with fiber in the form of coconut fiber mats and fiberglass mats, and the second type is a composite with fiber in the form of coconut fiber mats and WR (Woven Roving) fiberglass. The tensile test results show that the second type of composite is more recommended because of its higher strength and more consistent results. The test results show that the second type of composite has a tensile strength of 32.7 MPa, a flexural strength of 82.4 MPa, and is able to absorb impact energy of 2.34 Joules. And finally, in this research, the hybrid composite was made into a drone frame and then integrated with electrical components so that the drone can fly